2023
DOI: 10.3390/jcm12041320
|View full text |Cite
|
Sign up to set email alerts
|

Which Adverse Events and Which Drugs Are Implicated in Drug-Related Hospital Admissions? A Systematic Review and Meta-Analysis

Abstract: Adverse drug events (ADEs) and adverse drug reactions (ADRs) are leading causes of iatrogenic injury, which can result in emergency department (ED) visits or admissions to inpatient wards. The aim of this systematic review and meta-analysis was to provide up-to-date estimates of the prevalence of (preventable) drug-related ED visits and hospital admissions, as well as the type and prevalence of implicated ADRs/ADEs and drugs. A literature search of studies published between January 2012 and December 2021 was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…Evidence collected from one region in England has demonstrated that medication-related harm resulting in admission to hospital has more than doubled from 6.5% (95% CI 6.2% to 6.9%) in 2004 to 16.5% (95% CI 16.3% to 20.7%) in 2021 1 2. A recent meta-analysis (17 studies) estimated a prevalence rate of 8.3% (95% CI 6.4% to 10.7%) for adverse drug reaction (ADR)-related admissions and 13.9% (95% CI 8.1% to 22.8%) for adverse drug event-related admissions in similar studies worldwide 3. At least a third of ADRs may be preventable, although estimates of preventability vary between different studies because of case mix and the tools used to assess preventability.…”
Section: Introductionmentioning
confidence: 98%
“…Evidence collected from one region in England has demonstrated that medication-related harm resulting in admission to hospital has more than doubled from 6.5% (95% CI 6.2% to 6.9%) in 2004 to 16.5% (95% CI 16.3% to 20.7%) in 2021 1 2. A recent meta-analysis (17 studies) estimated a prevalence rate of 8.3% (95% CI 6.4% to 10.7%) for adverse drug reaction (ADR)-related admissions and 13.9% (95% CI 8.1% to 22.8%) for adverse drug event-related admissions in similar studies worldwide 3. At least a third of ADRs may be preventable, although estimates of preventability vary between different studies because of case mix and the tools used to assess preventability.…”
Section: Introductionmentioning
confidence: 98%
“…Propofol's anesthetic effects is exerted as an allosteric potentiator and agonist of the gamma-aminobutyric acid type A (GABAA) receptor, by potentiating the central inhibitory gamma-aminobutyric acid (GABA) neurotransmitter ( 8 ). There are some adverse drug reactions (ADRs) of propofol should be considered, such as pain on induction, hemodynamic instability as well as cardiovascular and respiratory depression in a dose-dependent way ( 9 ). Combining anesthetics could reduce both medication dosages and dose-related adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Alongside possible benefits, all medicines have the potential to cause harm, ranging from minor self-limiting problems to serious adverse effects requiring hospitalisation or worse. A recent meta-analysis estimated that about 10% of hospital admissions are related to adverse drug reactions and adverse drug events, with many being potentially avoidable 6. Prescribing errors constitute a substantial proportion of all medication errors (20% by one estimate),7 despite the optimisation of electronic prescribing 8.…”
mentioning
confidence: 99%